2003
DOI: 10.1080/01902140303785
|View full text |Cite
|
Sign up to set email alerts
|

IS MATERNAL COPPER SUPPLEMENTATION DURING ALVEOLARIZATION PROTECTING THE DEVELOPING RAT LUNG AGAINST THE ADVERSE EFFECTS OF MATERNAL NICOTINE EXPOSURE? A Morphometric Study

Abstract: In a previous study, it was shown that maternal nicotine exposure during gestation and lactation interfered with alveolarization and resulted in gradual deterioration of the lung parenchyma, resulting in microscopic emphysema. The aim of this study was thus to investigate the long-term effects of maternal nicotine exposure (1 mg/kg body weight/day, subcutaneous [sc] from the onset of the phase of rapid alveolarization, which occur from postnatal day 4 in rats, on (1) the development of the gas-exchange area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Exposure of fetal monkeys and rats to nicotine via the placenta during the late saccular/early alveolar phase of lung development results in an increase in the size and volume density of the primitive alveoli. As a consequence the alveolar surface area for gas exchange decreases (Collins et al, 1985;Maritz and Windvogel, 2003b). The structural changes in the lungs of these animals actually resemble faster aging of the lungs.…”
Section: Structural Developmentmentioning
confidence: 94%
“…Exposure of fetal monkeys and rats to nicotine via the placenta during the late saccular/early alveolar phase of lung development results in an increase in the size and volume density of the primitive alveoli. As a consequence the alveolar surface area for gas exchange decreases (Collins et al, 1985;Maritz and Windvogel, 2003b). The structural changes in the lungs of these animals actually resemble faster aging of the lungs.…”
Section: Structural Developmentmentioning
confidence: 94%
“…Alternatively, the fetal lung may be more susceptible than other organs to the growth-retarding effects of cigarette smoking. It is also reported that nicotine exposure during pregnancy and lactation results in impaired elastic tissue formation [25] , parenchymal damage [22] , slow alveolarization [26] , hyperplasia of bronchial muscle, mesenchymal changes, and a higher incidence of apoptosis [27] in neonatal lung. However, in these studies nicotine was given to the mother during both the pregnancy and during lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is also involved in antioxidant defences both extracellularly, when bound as ceruloplasmin (Al-Timimi & Dormandy, 1977;Goldstein et al, 1979;Gutteridge et al, 1980;A.D., Taylor & Oey, 1982), and intracellularly as a coenzyme for superoxide dismutase (Fridovich, 1978;Forsberg et al, 2001). Copper is also necessary in the diet to prevent inflammation (Denko, 1979) and emphysema in animal models (O'Dell et al, 1978), as well as reducing the adverse effects of maternal nicotine exposure on lung development in rats (Maritz & Windvogel, 2003), and so may also have a protective effect against COPD. Previous epidemiological studies have provided evidence supporting a protective effect of selenium on lung function (Hu & Cassano, 2000), but data on copper are much more limited (Sparrow et al, 1982).…”
Section: Introductionmentioning
confidence: 99%